A new fiscal pact, tax policy changes and income inequality: Latin America during the last decade - Giovanni Andrea Cornia; Juan Carlos Gómez-Sabaini; Bruno Martorano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The paper analyses the changes in tax policy, tax/GDP ratios, tax incidence and income inequality which have taken place in Latin America during the last decade against the background of the changes observed in these variables during the liberal years of the 1980s and 1990s. The paper argues that the recent tax policy changes and a favourable external environment led to an increase of about three points in the regional tax/GDP ratio, that such increase in taxation took place in a slightly or substantially more progressive way than in the past, that the Gini coefficient of the distribution of household income improved on average by 0.4-0.8 points, and that, as a result, redistribution via taxation improved (especially in the Southern Cone) in relation to the 1990s thanks to greater reliance on direct taxes and a reduction in excises. However, in the mid-late 2000s taxation remains unequalizing in about a third of the countries of the region, especially in Central America. The paper concludes by offering recommendations on how the new fiscal pact evolving in the region can be strengthened to improve the redistributive effect of taxation in the years ahead.
Keywords: D31; D70; H20; 330; tax policy; tax incidence; income inequality; redistribution; fiscal exchange; Latin America; Steuerpolitik; Steuerbelastung; Steuerinzidenz; Einkommensverteilung; Lateinamerika